2022
DOI: 10.1200/jco.22.01768
|View full text |Cite
|
Sign up to set email alerts
|

Reply to R. Nishihara et al

Abstract: On behalf of the EMERALD authors, we thank Nishihara et al 1 for their thoughtful comments on our study. 2 We agree that elacestrant may provide a significant new treatment option to address an unmet medical need for patients with estrogen receptor-positive/human epidermal growth factor receptor 2-negative metastatic breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…While alisertib did not restore sensitivity to fulvestrant as preclinical studies 5,6 conducted before the CDK 4/6i era had suggested, it is feasible the hypothesis was not fairly tested given that accumulating clinical data demonstrate minimal antitumor activity of endocrine monotherapy following CDK 4/6i progression 17,24 and the fact that the entire cohort received prior CDK 4/6i therapy. Furthermore, the role of continued ER block- ade in combination with targeted therapies after CDK 4/6i progression is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While alisertib did not restore sensitivity to fulvestrant as preclinical studies 5,6 conducted before the CDK 4/6i era had suggested, it is feasible the hypothesis was not fairly tested given that accumulating clinical data demonstrate minimal antitumor activity of endocrine monotherapy following CDK 4/6i progression 17,24 and the fact that the entire cohort received prior CDK 4/6i therapy. Furthermore, the role of continued ER block- ade in combination with targeted therapies after CDK 4/6i progression is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…24 In the phase 3 EM-ERALD trial, the oral selective ER degrader elacestrant was associated with a significantly improved mPFS compared with standard ET (fulvestrant or AI); however, mPFS was only 2.8 months. 17 In the BYLieve trial, a single-arm study of alpelisib with fulvestrant in patients with CDK 4/6i-resistant, PIK3CAvariant, ER + MBC, those with measurable disease (n = 100) had an ORR (calculated as best overall response) of 21% (95% CI, 14%-30%) and a 24-week CBR of 42% (95% CI, 35%-52%). 25 In the overall cohort (n = 121), including those with the more clinically favorable nonmeasurable disease, mPFS was 7.3 months; (95% CI, 5.6-8.3) and mOS was 17.3 months (95% CI, 17.2-20.7).…”
Section: Discussionmentioning
confidence: 99%
“…The eligible population in this study utilized the sample characteristics of the EMERALD clinical trial: Participants were advanced/metastatic ER+/HER2-breast cancer; Their disease has progressed or relapsed on or after 1 or 2 lines of endocrine therapy, 1 of which was given in combination with a CDK4/6 inhibitor, for advanced or metastatic breast cancer; The ECOG PS 0 or 1 (11).…”
Section: Cohort Patientsmentioning
confidence: 99%
“…The subgroup was included to compare the effectiveness of treatment between different groups of patients with detectable ESR1 mutations (16). EMERALD was an international, randomized, open-label, activecontrolled, Phase III clinical study (11) (NCT03778931) accessing the efficacy and safety of an investigational oral hormone therapy, ELA (RAD1901), to the SOC hormone therapy options of FUL or an AI in patients with A/MBC that expresses the ER-positive and does not express HER2. In the EMERALD trial, patients treated with ELA had better progression-free survival (PFS) than patients treated with FUL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation